THE EFFECT OF DIFFERENT LIGHT COLORS ON THE BIOMASS GROWTH OF Spirulina platensis - Hanryani, Putri; Efriyeldi, Efriyeldi; Effendi, Irwan (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2019)
Spirulina is microalgae that spreads widely in nature and can be found in various types of environments, both in brackish, sea and fresh water. Spirulina is photoautotrophic, so it requires light as an energy source for cell growth and synthesis of various important substances involved in it. Lack of light can cause photosynthesis to not take place normally so that it will affect the growth of S. platensis. This study aims to determine the effect of different light colors on the biomass growth of S. platensis. This research was conducted from March to April 2019 at the Marine Microbiology Laboratory and the Marine Chemistry Laboratory, Faculty of Fisheries and Marine, Universitas Riau. The method used in this research was the experimental method. The study design used was a completely randomized design (CRD) with four treatments (red, yellow, blue and control colors) and three replications. The results showed that the light colors had a significant effect on the biomass growth of S. platensis. Yellow light gave the best biomass growth, followed by red and blue light.